Reduced‐order observer‐based controller design for quasi‐one‐sided Lipschitz nonlinear systems with time‐delay - Dong, Wenqiang; Zhao, Yanbin; Cong, Yuhao (International journal of robust and nonlinear control, 2021)
Summary In this article, the problem of reduced‐order observer‐based controller design for a class of nonlinear time‐delay systems is addressed. First, we present sufficient conditions for the existence of the reduced‐order observer of nonlinear time‐delay systems. Then, a state feedback controller is designed to stabilize the systems. Furthermore, it is shown that the separation principle holds for stabilization of the systems based on the reduced‐order observer‐based controller. When the nonlinear part of systems satisfies the quasi‐one‐sided Lipschitz condition, the reduced‐order observer and feedback controller can be designed separately even though the parameter (A, C) of systems is not detectable and parameter (A, B) is not stabilizable. Finally, a numerical example is presented to show the effectiveness of the proposed approach.